The Future is Now From Before: Youth Climate Activism and Intergenerational Justice - Theodorou, Eleni; Spyrou, Spyros; Christou, Georgina (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2023)
This paper draws on data from a qualitative study of youth climate activists in Cyprus to explore the notion of temporality implied in how youth interrogate intergenerational relations in the context of their struggle against climate change and the tensions therein. Acknowledging the structural age inequalities that limit their actions, youth activists drew on multiple temporal frames of present, future, and past to delineate a sense of urgency for action to prevent an irreversible catastrophe in the future and to forge a future of hope. In the process, they invited other/older generations to the climate struggle, an opening that came with expressions of ambivalence among some activists.